Rantai Pasok Beras Di Desa Mopuya Utara Kecamatan Dumoga Utara Kabupaten Bolaang Mongondow (Studi Kasus: Desa Mopuya Utara) - Tarumingkeng, Flandio Geraldine; Talumingan, Celcius; Rori, Yolanda Pinky Ivanna (AGRI-SOSIOEKONOMI, 2024)
The study aimed to determine the product flow, financial flow and information flow of the rice supply chain in North Mopuya Village, North Dumoga Subdistrict, Bolaang Mongondow Regency. The research was conducted for 2 months, from July to August 2023. The research was conducted in Mopuya Utara Induk Village, North Dumoga Subdistrict, Bolaang Mongondow Regency, North Sulawesi. The data used in the study were primary data collected by conducting documentation, observation and direct interviews using a list of questions (questionnaire), and secondary data collected through the results of literature studies and related offices or agencies. The sampling method used by purposive sampling method was taken 7 farmers, after selecting 7 farmers continued with the snowball sampling method to know the institutions involved in the supply chain. The data analysis method used in this research is the analysis of the flow of the rice supply chain in North Mopuya Village, North Dumoga Subdistrict, Bolaang Mongondow Regency which is presented in a descriptive form that describes and explains the research subject. The results showed that the rice supply chain in North Mopuya Village, North Dumoga Subdistrict, Bolaang Mongondow Regency based on product flow, financial flow and information flow has been running very well, starting from farmers as producers to the community as consumers.